The Titan's curse - Riordan, Rick. (New York : Hyperion Paperbacks for Children, 2008)
The disappearance of the goddess Artemis while out hunting a rare, ancient monster, prompts a group of her followers to join Percy and his friends in an attempt to find and rescue her before the winter solstice, when her influence is needed to sway the Olympian Council regarding the war with the Titans.
4.7
5-8
5-8.
Wilson's Junior High School
School Library Journal
Book Links (A.L.A.)
Keywords: Jackson, Percy (Fictitious character) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Artemis (Greek deity) -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Monsters -- Juvenile fiction; Titans (Mythology) -- Juvenile fiction; Jackson, Percy (Fictitious character) -- Fiction; Mythology, Greek -- Fiction; Animals, Mythical -- Fiction; Monsters -- Fiction; Fantasy; Jackson, Percy (Fictional character) -- Fiction; Greek mythology -- Fiction; Mythical animals -- Fiction; Monsters -- Fiction; Fantasy fiction; Fantasy fiction